Self-determination and study involvement: an empirical study - Hassan, Arif (s.n, 2013)
The study examines the role of learning climate (autonomy supportive vs. controlling), intrinsic motivation resulting from the three basic needs satisfaction (as posited by Self Determination Theory of motivation), self-perception of choice and self-awareness on students study engagement and academic performance (measured in term of CGPA). The study intended to test the validity of Self Determination Theoty (SDT) in the Asian and Islamic cultural and institutional context. The data were collected from 529 undergraduates Muslim student (Female = 57.7% and 81.7% Malaysia) representing several study disciplines. Standardized instruments were employed to measure the constructs of learning climate, basic needs, perceived self-determination, and study engagement. Result provided strong support to the SDT proposition suggesting that an autonomy supportive learning climate significantly contributed to intrinsic need satisfaction of autonomy, competence, and relatedness